ENT600 : iDxPar / Abdul Wafi Zakaria, Mohamad Syahirul Fazli Mansor and Mohd Fakhrul Arif Mohamad - Zakaria, Abdul Wafi; Mansor, Mohamad Syahirul Fazli; Mohamad, Mohd Fakhrul Arif (2018)
iDxPar is device that can be used to detect stool in disposable diapers. This device will allert parents about the stool content thus will ensure that the rashes among babies in this country can be decrease resulting in increasing of healthy babies. The target market for this device is for the Malaysian parents with below than 3 years old kids.